2001
DOI: 10.1074/jbc.m008528200
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide-induced Structural Alterations of RNase A

Abstract: Proteins exposed to oxidative stress are degraded via proteolytic pathways. In the present study, we undertook a series of in vitro experiments to establish a correlation between the structural changes induced by mild oxidation of the model protein RNase A and the proteolytic rate found upon exposure of the modified protein toward the isolated 20 S proteasome. Fourier transform infrared spectroscopy was used as a structure-sensitive probe. We report here strong experimental evidence for oxidation-induced confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 62 publications
9
63
0
Order By: Relevance
“…Since it is assumed that various oxidants are involved in the formation of various forms of oxidized proteins, it seems to be clear that there should be a common recognition mechanism. It was proposed by the groups of Stadtman and Davies (118)(119)(120) and later confirmed by our group (121)(122)(123)(124) that this common recognition motive is the exposure of hydrophobic amino acids to the surface of the protein, which means at least a partial unfolding of the substrate. The arings of the 20S ''core'' proteasome are responsible for substrate recognition and binding.…”
Section: The Degradation Of Oxidized Proteins-a Function Of the 20s Psupporting
confidence: 59%
“…Since it is assumed that various oxidants are involved in the formation of various forms of oxidized proteins, it seems to be clear that there should be a common recognition mechanism. It was proposed by the groups of Stadtman and Davies (118)(119)(120) and later confirmed by our group (121)(122)(123)(124) that this common recognition motive is the exposure of hydrophobic amino acids to the surface of the protein, which means at least a partial unfolding of the substrate. The arings of the 20S ''core'' proteasome are responsible for substrate recognition and binding.…”
Section: The Degradation Of Oxidized Proteins-a Function Of the 20s Psupporting
confidence: 59%
“…Oxidized protein degradation by the 20 S proteasome has been studied extensively by different groups (20,(52)(53)(54)(55). Mild oxidation leads to an increased proteolytic susceptibility, whereas highly oxidized protein becomes resistant to degradation by the 20 S proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that mildly oxidized proteins exhibit decreased thermal and thermodynamic stability (56,57) and bind more efficiently the hydrophobic fluorescent probe ANSA (40). Both the exposure of hydrophobic surface on modified proteins and the loss of secondary structure have been proposed to act as a recognition signal for binding and degradation of the substrate protein by the 20 S proteasome (19,54,55). Because glycated proteins are poor substrates of the 20 S proteasome, structural studies of the glycated forms of G6PDH aimed at assessing their secondary and tertiary structure as well as their conformational stability were performed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the 26S proteasome, the 20S proteasome is able to recognize unfolded proteins and, therefore, oxidized proteins, due to their increased surface hydrophobicity ( Fig. 2) (52,95,128). On the other hand, the 20S proteasome seems to be more resistant to oxidative stress than the 26S proteasome (137,138).…”
Section: Repair and Degradation Of Oxidized Proteinsmentioning
confidence: 99%